ANALISIS TINGKAT KESEHATAN KEUANGAN PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Yati, Sri (Fakultas Ekonomi, UIN Maliki Malang, 2012)
The competitive advantages of the companyâ€™s are mainly determined by the performance. One important aspects of performance is financial aspects which are illustrated in financial statements. However, it is not enough to only assess the financial performance of companies. It required the analysis of financial statements to obtain the whole picture of companyâ€™s progress which is can be used by management or other users of financial statements to make decision making. The financial analysis in this research is used Z-Score to determine the company's financial performance more accurately and the health level of cigarettes companies in facing global competition and also dealing with the smoking ban regulations. The research was conducted on three tobacco companies that go public on the Stock Exchange Indonesia, that are PT Bentoel International Tbk., PT. Gudang Garam Tbk., PT. Hanjaya Mandala Sampoerna Tbk.Â Z-Score results showed that PT Bentoel International Tbk in 2008 and 2009 had a poor financial performance and classified as highly vulnerable company, whereas in 2010 the company was in a good performance and healthy condition. Meanwhile, PT Gudang Garam Tbk from 2008, 2009 and 2010 is classified as healthy company. PT. Hanjaya Mandala Sampoerna Tbk has a good financial performance and categorized as healthy company began in 2008, 2009 to 2010. To conclude, among the three tobacco companies that go public on the Stock Exchange Indonesia, PT Hanjaya Mandala Sampoerna Tbk is a company that has the best financial performance and classified as a healthy company.